2022
DOI: 10.26434/chemrxiv-2022-pcn8c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatially resolved top-down proteomics of tissue sections based on a microfluidic nanodroplet sample preparation platform

Abstract: Conventional proteomic approaches measure the averaged signal from mixed cell populations or bulk tissues, leading to the dilution of signals arising from subpopulations of cells that might serve as important biomarkers. Recent developments in bottom-up proteomics have enabled spatial mapping of cellular heterogeneity in tissue microenvironments. However, bottom-up proteomics cannot unambiguously define and quantify proteoforms, which are intact (i.e. functional) forms of proteins capturing genetic variations,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
1
Order By: Relevance
“…But the overlap of the proteoforms detected in LCMS and MALDI is essential for proteoform assignment. In contrast to our recent study of rat brain where most peaks were annotated, (Liao et al, 2022), only a few peaks in these MALDI data were confidently assigned to the identified proteoforms. Some of the unassigned species are likely from artifacts such as oxidation and sodium adduction.…”
Section: Msi Maps Spatial Distribution Of Proteoforms In Tissue Sectionscontrasting
confidence: 77%
“…But the overlap of the proteoforms detected in LCMS and MALDI is essential for proteoform assignment. In contrast to our recent study of rat brain where most peaks were annotated, (Liao et al, 2022), only a few peaks in these MALDI data were confidently assigned to the identified proteoforms. Some of the unassigned species are likely from artifacts such as oxidation and sodium adduction.…”
Section: Msi Maps Spatial Distribution Of Proteoforms In Tissue Sectionscontrasting
confidence: 77%